Welfare Effects of Salary Forecast Error in Professional Labour Markets - Freebairn, John W.; Withers, Glenn A. (The Review of Economics and Statistics, 1979)
FOR occupations requiring long training periods salary forecast errors can produce significant costs. This paper uses the recursive model of professional labour markets to describe the nature and magnitude of these costs and their distribution between the suppliers and demanders of skilled labour. A analysis for two professional labour markets-lawyers and engineers-is used to illustrate application of the models for estimating the potential benefits of more accurate forecasts of professional salaries. Since the attainment of professional qualifications involves long training periods, realised salaries can differ substantially from those anticipated when the decisions to undertake training were made. Recent studies' have exploited this time delay in the production of graduates and the influence of market forces on training entry and on graduate hiring decisions to analyse skilled labour markets. In these studies the number of new graduates depends on forecasts of salaries formed at the beginning of training periods. This predetermines the supply of new graduates for given period. Realised salaries are assumed to adjust so as to clear the market. A recursive structure is thereby established which generates endogenous cyclical fluctuations in the number of new graduates and their beginning salaries. Exogenous shocks to demand and supply also influence the levels of salaries and new graduates. In such markets salary forecast error is likely to arise and to result in losses to the suppliers and buyers of skilled manpower relative to the levels achievable in state of more accurate forecasts. This paper uses standard economic surplus techniques to specify these losses and to portray the costs of misinformation in some concrete occupational examples. In this way the problems of occupational forecasting error and labour market decision-making are placed in quantitative framework. It is fully recognised that surplus-based measures of welfare are not a branch of moral arithmetic that lead mechanically or automatically to any normative conclusion (Hause, 1975, p. 1146). Rather, we seek to produce description based on relevant and consistently defined measure relating to the change in an individual's situation when the set of prices facing the individual are altered. We accept the justification for such measures advanced by Harberger (1971) and others.2